Onsite Tests and Numerical Simulation of Broken Rock Zones in Surrounding Rocks of Seepage Roadways under Blasting. (22nd December 2020) - Ye, Zhouyuan; Pan, Kun; Zhou, Zhihua
Abstract : To study the influence of blasting vibration on the broken rock zone around a seepage roadway and provide guidance for design of the roadway support, the broken rock zones around rock of seepage roadways under production blasting vibration are determined by onsite tests in a mining area, Daye iron mine. During the testing process, it is found that blasting vibration causes internal cracks of surrounding rocks to initiate and develop, the fracture density increases, the acoustic wave velocity of rock mass decreases, and the broken rock zones expand. At the same time, through onsite observation, it is found that blasting vibration results in crack development and formation of a water pathway to lead to surface water into the ground. The mechanical response around rock of the seepage roadway under blasting vibration is simulated by the two-dimensional realistic fracture progress analysis calculation software (RFPA 2D ). It is found that internal cracks of roadway surrounding rock initiate, propagate, and join up gradually, and the fracture range is expanding under the seepage water pressure, ground stress, and cyclic loads, and the broken rock zones also expand. The results from numerical simulation are consistent with the results of onsite tests. It is also found that the tensile stress appears around some cracks, leading to part of the cracks more likely to generate shear failure under the seepage water pressure during simulation.